"Caught between a Rock and a Hard Place": How Kenyan Journalists are Coping with Pressure for Media Accountability. Issue 2 (3rd April 2019) - Obuya, Jared; Ong'ondo, Charles
ABSTRACT: Globally, there are growing demands on the news media to remain accountable to the public. This scenario arises mainly due to the empowerment of citizens and advances in technology. This article reports findings from a multiple case study that investigated how journalists from two Kenyan media houses are coping with the demands for media accountability. It specifically responds to two questions: How are media accountability policies and practices implemented in media houses in Kenya? What challenges face media accountability in Kenyan newsrooms? Data was generated through in-depth interviews with 16 journalists purposively selected from the newsrooms of the two media houses. It was analysed thematically and presented in narrative form. The findings show that although the media houses have various accountability policies and practices in place, their implementation is weak and inconsistent. Furthermore, a number of obstacles challenge efforts towards media accountability in the media houses, including institutional weaknesses and interference by vested interests. Consequently, the existing media accountability policies and practices have not improved the quality of journalism in the media houses. These findings imply that there is a need for well-negotiated, clearly documented and firm measures and incentives to encourage media organizations to invest in media accountability.